2000
DOI: 10.1258/0004563001899014
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of haptoglobin phenotypes in a Korean population, using the semi-automated PhastSystem

Abstract: SUMMARY.We have established a new phenotyping method for haptoglobin, based on sodium dodecyl sulphate±polyacrylamide gel electrophoresis using the PhastSystem (Pharmacia Biotech, Uppsala, Sweden), followed by immunoblotting for detection. We measured haptoglobin concentrations and determined the haptoglobin phenotypes of 316 healthy Koreans using this method: 31 (9´8%) were of Hp 1-1 type, 140 (44´3%) of Hp 2-1 type and 145 (45´9%) of Hp 2-2 type. The haptoglobin allele frequencies were calculated to be 0´32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…4 However, electrophoresis phenotyping could not discriminate between hypohaptoglobinaemia and true anhaptoglobinaemia. In our study, Hp 0 Hp 2 , but not Hp 0 Hp 1 , was shown to be associated with hypohaptoglobinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, electrophoresis phenotyping could not discriminate between hypohaptoglobinaemia and true anhaptoglobinaemia. In our study, Hp 0 Hp 2 , but not Hp 0 Hp 1 , was shown to be associated with hypohaptoglobinaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Haptoglobin phenotypes were determined in a blinded fashion from serum samples. We modified the phenotyping method for haptoglobin established by Yang et al [21] based on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) of sera followed by immunoblotting. Haptoglobin molecules were separated and identified using 5%-10% gradient gels (Hoefer SG 15 gradient maker; San Francisco, CA).…”
Section: Haptoglobin Phenotype/genotype Analysismentioning
confidence: 99%
“…Analyses were performed on sera frozen at -70 • C. Hp concentration was measured using the nephelometric method on a Cobas Integra 700 (Roche, Basel, Switzerland). We modified the phenotyping method for Hp established by Yang and coworkers [17], based on sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) of sera followed by immunoblotting. Hp molecules were separated and identified using 5%-10% gradient gels (Hoefer SG 15 gradient maker; San Francisco, CA, USA).…”
Section: Haptoglobin Phenotype Analysismentioning
confidence: 99%